Analysis of foreign experience in the innovation and investment development of agriculture - Khatamova Manzura Ochildiyevna, (THE INNOVATION ECONOMY, 2026)
The article examines and systematizes the experience of a number of leading foreign countries in the innovation and investment development of the agricultural sector. It analyzes the changes in the sources of financing investments attracted to agriculture, forestry, and fisheries in our country. Scientifically grounded proposals have been developed to improve the mechanism of attracting investments in this sector.